Time to achieve optimal glycemic control and its determinants among diabetes mellitus patients receiving treatment: a retrospective study - Maru Zewdu Kassie; Chekol Alemu; Habitamu Wudu; Buzuneh Tasfa Marine; Asaye Alamneh Gebeyehu (Scientific Reports)
Abstract Diabetes mellitus (DM) is a major public health problem responsible for morbidity and mortality. Maintaining blood sugar control helps patients achieve optimal glycemic levels. Therefore, this study aimed to identify the factors affecting the time to achieve optimal glycemic control among DM patients at Assosa General Hospital (AGH), Western Ethiopia. A retrospective study design was conducted from 427 randomly selected DM patients in the outpatient department (OPD) clinic at AGH under the follow-up period from September 2022 to September 2024. The median survival time, Kaplan-Meier survival estimate, and Log-Rank test were used to describe the data and compare the survival time between groups. The study used Cox PH model to analyze the time to achieve optimal glycemic control of DM patients, where hazard ratio, p-value, and 95% CI for hazard ratio were used for testing significance. Schoenfeld and Cox-Snell residuals were used to check the model assumptions. The median time to optimal glycemic control for DM patients was 12 months. At the end of the follow-up, 74.2% of the patients had developed an event and the rest 25.8% were censored. The significant predictors of time to optimal glycemic control include: older age (AHR = 0.871(95% CI 0.809, 0.937)), females (AHR = 1.295 (95% CI 1.024, 1.639)), having FHDM (AHR = 1.681(95% CI 1.313, 2.153)), rural residence(AHR = 0.463(95% CI 0.354, 0.607)), presence of comorbidity (AHR = 0.508(95% CI 0.302, 0.854)), DM related complications (AHR = 0.419(95% CI 0.326, 0.539)), high BLBGL AHR = 0.997(95% CI 0.995, 0.998)). This study found the factors that prolonged or shortened the time to reach optimal glycaemic control for T2DM patients. The study revealed that older age, male patients, patients having other related comorbidities and patients with no FHDM, patients having DM-related complications as poor prognostic factors of T2DM disease and also prolonged recovery time. Therefore, attention should be given to these patients to obtain good glycaemic levels and the patient being healthy.